A methods engineering study on Miracle Candle Factory - Agbay, Arnel; Baqueriza, Nikki Lou.; Domingo, Gay. (Diliman, Quezon City College of Engineering, 2000)
The Miracle Candle Factory, based on Cainta, Rizal, manufactures vigil glass candles, decorative or spiral candles, ordinary, and cylindrical candles. The group chose the glass type of candle as the primary focus of the study based on the products' profit share. Through the use of the Streamline Diagnosis Chart and Ishikawa diagram, the following problems were identified; excessive workers' idle time, excessive movement of materials and production delays. At most three alternatives were generated for each aforementioned problem. A common alternative for the three problems is to do nothing. To reduce the idle time of workers, it is suggested that a schedule should be made for the workers in the glass department or a strict implementation of the "non-piece-rate" of work during the workers free time. For excessive movement of materials, it is recommended that the material handling system should be improved or a revision of the plant layout. To reduce the delays in production, the setting of standard times for the processes and a revision of the plant layout or the procurement of bottles from outside suppliers are suggested. All the alternatives were evaluated using the Kepner-Tregoe Decision analysis and Cost-Benefit Analysis. Evaluation of the alternatives show that in order to reduce the idle time of workers, a worker's schedule should be made. Also, to avoid production delays, standard times should be set and the plant layout should be revised. Plant layout revision is also recommended to reduce excessive movement of materials. Time study was used to determine the standard time for the production of the glass candles. Finally, implementing steps for each recommendation was presented.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Systems analysis